A new species of Chaetozone (Polychaeta, Cirratulidae) from Europe, with a re-description of Caulleriella zetlandica (McIntosh) - Woodham, Annette; Chambers, Susan (Mémoires du Muséum national D'histoire naturelle, 1994)
Chaetozone setosa Malmgren, 1867 is common in soft sediments from the intertidal zone to the deep sea and is recorded as having a cosmopolitan distribution. It has been apparent for some time that more species of Chaetozone may be present than are currently recognised. During benthic monitoring in the English Channel, a distinct species of Chaetozone, C. gibber sp. nov. was recognised. The new species is described in detail and distinguished from C. setosa. As Caulleriella zetlandica (McIntosh, 1911) is similar in overall appearance and lacks a full description, this species is re-described from material obtained near the type locality. Although the spines of both species are unidentate in fully grown individuals, C. zetlandica can be distinguished from C. gibber by the lack of spines in the notopodia. The need for re-definitions of the genera Chaerozone and Caulleriella is discussed.
World Polychaeta Database (WPolyDb)